2021
DOI: 10.1186/s12888-021-03460-3
|View full text |Cite
|
Sign up to set email alerts
|

Radically open dialectical behaviour therapy adapted for adolescents: a case series

Abstract: Background Overcontrol is a transdiagnostic cluster of traits associated with excessive psychological, behavioural and social inhibitory control. It is associated with psychiatric diagnoses of depression, restrictive eating disorders and/or obsessive-compulsive personality disorder. Radically Open Dialectical Behaviour Therapy is a transdiagnostic treatment for maladaptive overcontrol. This case series evaluates an adolescent adaption (RO-A) for a transdiagnostic group of adolescents identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Their results found significant decreases in depressive symptomatology post-treatment, but these gains were not maintained at follow-up (Lynch et al, 2019). Baudinet et al (2021) found significant changes in the FFOCI-SF post-treatment in adolescents who were assessed to be overcontrolled and received an adaptation of RO DBT.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Their results found significant decreases in depressive symptomatology post-treatment, but these gains were not maintained at follow-up (Lynch et al, 2019). Baudinet et al (2021) found significant changes in the FFOCI-SF post-treatment in adolescents who were assessed to be overcontrolled and received an adaptation of RO DBT.…”
Section: Discussionmentioning
confidence: 94%
“…The selection of outcome measures for a novel intervention is challenging (Coster, 2013), and as overcontrol is a relatively new concept, there was a lack of specific measures related to this area. The measures in the current study were chosen based on their ability to determine overall traits of overcontrol and associated psychopathology (Baudinet et al., 2021; Hempel et al., 2018; Lynch et al., 2019). Additional measures were included to capture change in the three themes that are targeted in GRO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptations of RO DBT have recently been described and evaluated using uncontrolled case series designs in both the outpatient [ 21 ] and day patient setting [ 7 ] for adolescents with eating disorders, anxiety and/or mood difficulties. In both treatment contexts improvements are observed in psychiatric symptoms (eating disorder and mood), relationship quality, social withdrawal, cognitive flexibility, reward sensitivity and the maladaptive use of emotional suppression to regulate emotions [ 7 , 21 ]. These adaptations were based on informal feedback from adolescents that some of the RO DBT materials were more relevant for adults.…”
Section: Introductionmentioning
confidence: 99%
“…These adaptations were based on informal feedback from adolescents that some of the RO DBT materials were more relevant for adults. Adaptations in these uncontrolled case series’ include shortening treatment length (20 skills classes in the outpatient setting; 16 in a day patient setting instead of 30 skills classes), shorter classes (60–90 min vs 2.5 h) and amending materials to include more adolescent-focused examples and teaching materials [ 7 , 21 ]. This fits with the current study, in which RO DBT was very slightly amended (see method section).…”
Section: Introductionmentioning
confidence: 99%